ANALISIS KESALAHAN MAHASISWA PADA MATERI FUNGSI DUA PEUBAH DENGAN NEWMANN’S ERROR ANALYSIS (NEA) - Nur Baiti Nasution (Delta: Jurnal Ilmiah Pendidikan Matematika, 2018)
The aim of this article is to describe the student’s error using Error Analysis (NEA) in Multivariable Calculus course. For analyzing the error, we analyzed the student’s finel test work. The analysis was held in two steps, qualitative and quantitative. Qualitative part was done when categorizing the error based on NEA, which are reading, comprehension,transformation, process skill, and encoding. As the data triangulation, we also interviewed the students to conﬁrm the analysis results. From the analysis and interview, it was known that the errors were happened because the lack of basic algebra ability and the lack of ability of ﬁnding the function derivative.